Synthesis of Highly Substituted 3-Acylpyrroles by a Four-Component Sonogashira Alkynylation–Amine Addition–Nitroalkene Michael Addition–Cyclocondensation - Schmitz, G. Hendrik; Lampiri, Panagiota; Müller, Thomas J. J. (Synlett, 2023)
A consecutive four-component alkynylation–amine addition–nitroalkene addition–cyclocondensation one-pot reaction of acid chlorides, alkynes, amines, and nitroalkenes furnished a library of 3-acylpyrroles in modest to good yields. The sequence takes advantage of a synergism between a Brønsted acid (acetic acid) and a Lewis acid [iron(III) chloride] in the terminal addition-cyclocondensation step of the intermediately formed enaminones with nitroalkenes.
Keywords: alkynylation; copper catalysis; cyclocondensation; multicomponent reaction; cascade reaction; pyrroles